Belonging Together Separately: Transforming Indigenous Health Policy to Increase Substantive Equity - George, Sherry A. (Scholarship@Western, 2023)
This Organizational Improvement Plan (OIP) seeks to address a Problem of Practice (PoP) focusing upon the lack of Indigenous involvement in federal health policy development. The application of critical theory to change model development, implementation, and evaluation with a collaborative inquiry lens guides this discussion. Leadership theories reflective of Indigenous values will be utilized. Consideration of a more equitable approach to healthcare for First Nations, not as an add-on to existing mainstream models but as its own paradigm, has assisted in developing key Indigeneity grounded themes in this writing which centre on knowledge transfer, empowerment, and partnership as important components for Indigenous health policy frameworks. The Indian Health Transfer Policy, which governs comprehensive agreements, is a top-down, structural functionalist approach focused upon the most feasible use of funding. Scientific, evidence-based data that informs responsible and accountable health practice is invaluable and this is not contested within Indigenous-driven models. Historically, in practice, assessment and treatment arising from research has primarily legitimized colonial discourse with Indigenous Knowledge (IK) relegated to an unconventional way of knowing. Much of the change initiatives that have been attempted, while perhaps from a culturally sensitive framework, have neglected two key factors: 1) the embodiment of an approach that reflects Indigenous perspectives (e.g., Two-Eyed Seeing); and 2) the Eurocentric worldview (context) within which First Nations communities must navigate health and wellness. Most often, EDID work is performative and acknowledges diversity, but fails to understand the harm resulting from viewing Indigenous ways of knowing as being tantamount to “culture”. Transformative work must be reflective of the community’s values and vision for wellness and acknowledge their worldview.